Managing and Mitigating Suffering in the Return-to-Work Process - Woods, Megan; Matthewson, Mandy L. (Frontiers in Psychology, 2021)
Each year thousands of workers experience a serious illness or injury that necessitates time off work and a subsequent re-engagement with the work environment. In Australia, worker’s compensation legislation mandates the return-to-work (RTW) process is formal, structured, and negotiated between the worker, their employer, health care professionals and their return-to-work coordinator. How this is executed by those parties directly influences whether the RTW process is supportive and successful, or exacerbates the suffering of returning workers by causing them to feel ostracised, exposed and vulnerable in their workplace. In this paper, we examine how the RTW process can cause physical, emotional, social, and existential suffering for returning workers. We then discuss how the suffering that workers experience can be mitigated by five key factors: clarity of roles in the RTW process, alignment of worker and employer expectations, the advocacy provided by the RTW coordinator, the support provided for the worker’s psychological wellbeing, and the RTW literacy of supervisors and colleagues.